An evaluation of the Tekscan I-Scan System for the assessment of tongue movement during oral processing of semi-solid foods - Liang, Xinyue (2012)
The main objective of this dissertation is to evaluate the scope of a commercial pressure sensor device, the Tekscan I-Scan System (Tekscan, South Boston, MA, USA), to study tongue movement whilst eating foods that are predominantly manipulated with the tongue during oral processing. Initially, methodology to use the sensor sheet in mouth had to be developed as this application of the system was novel. To measure tongue pressures the approach of fixing the sensory sheet, wrapped into cling film to protect it from saliva and food residues, to the upper palate was taken. Ten subjects were then asked to consume seven selected semi-liquid / semi-solid commercial food products with the sensor fixed in place. The foods ranged from liquid to gel-like and their textural attributes were analyzed instrumentally. The data sets obtained with the Tekscan I-Scan System included pressure, area and force data over sampling time. Initial and final values, mean values and peak values as well as average values were provided. Area data referred to the pressure cells that had been activated by the probe (attached on the tongue). To assess the scope of the Tekscan I-Scan system relationships between the results from texture analysis and in-vivo measurement were explored through principle component analysis. The tongue pressure distribution during whole eating process is available as movie recordings. This revealed higher pressure distributed near the gums of two sides of molars at the time of maximum contact pressure between tongue and palate while pressure was distributed in the middle region of the palate in other periods. Also, the time of maximum tongue variables attained was close to 70% of whole eating duration and it was interpreted as the moment the subject swallowed. The frequency of tongue moving rhythm was one per second and tongue pressures were produced evenly whether food was consumed in oral cavity or no sample was present in mouth. Total contact pressure and number of contact pressure peaks showed linear correlations to finish time as well as the textural properties. This research shows that the behavior of tongue movement was comparatively stable during eating process independent of subjects and the kinds of semi-solid foods, except for the moment that maximum contact pressure was recorded which implied swallow was happening. The textures of the selected products are not all differentiated obviously but there are close correlative PCA results with some tongue variables. Linear relationships between texture data and tongue variables reveal the high interaction between food texture and tongue manipulation. The capacity of Tekscan I-Scan System on the study of tongue movement is proved. However, the shape of sensor sheet and the sensory assessment of food texture are the two main works in the future for further study of tongue movement.